Creating Augmented Reality Teaching Materials to Support a Local Wisdom-Based Curriculum in Secondary Schools - Pattaufi; Makawi, Faizal Erlangga; Aswan, Dedy; Hisanan, Herawan (Cita konsultindo, 2025)
Teaching materials that integrate Augmented Reality for developing teaching and learning based on local wisdom in secondary schools are highly important. Students gain access to learning about their local wisdom, supporting the implementation of the curriculum. However, the lack of teaching materials to support the implementation of this core curriculum becomes a major obstacle for teachers. The method of this research utilizes a descriptive qualitative research method with the implementation of the conceptual framework by Freeman (1998). Data collection techniques include observations, interviews, and questionnaires from 130 students. Teachers, art practitioners, and students in Toraja city, South Sulawesi Province, are the samples of this research. The research results show that; (1) Teaching materials are incomplete, such as videos being unavailable; (2) Artwork dimensions dominate the conceptual framework analysis, while in the four frames analysis, both subjectivity and structural aspects appear frequently ; (3) Questionnaires show an average of 3.00 in students' recent understanding of their cultural wisdom ; (4) This research provides six steps to create Augmented Reality. Implementing Augmented Reality is beneficial for both teachers and students. It provides learning opportunities that support the implementation of the curriculum based on local wisdom.